1998
DOI: 10.1006/toxs.1997.2368
|View full text |Cite
|
Sign up to set email alerts
|

Uranyl Nitrate: 91-Day Toxicity Studies in the New Zealand White Rabbit

Abstract: These studies were undertaken to derive a lowest-observed-adverse-effect level (LOAEL) in the New Zealand White rabbit following a 91-day exposure to uranium (U, as uranyl nitrate hexahydrate, UN) in drinking water. Males were exposed for 91 days to UN in their drinking water (0.96, 4.8, 24, 120, or 600 mg UN/L). Subsequently, females were similarly exposed for 91 days (4.8, 24, or 600 mg UN/L). Control groups were given tap water (< 0.001 mg U/L). Regular observations were recorded, and urine was collected pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…There is no evidence for glomerular injury (Kurttio et al 2002). Evidence for dose-related proximal tubular injury has been observed after both ingestion and injection of uranium in animal (Diamond et al 1989; Gilman et al 1998) as well as in human (Zamora et al 1998) studies. The histopathologic damage to the proximal tubules is manifest as cytoplasmic vacuolation, interstitial scarring, and destruction of the basal lamina (Gilman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence for glomerular injury (Kurttio et al 2002). Evidence for dose-related proximal tubular injury has been observed after both ingestion and injection of uranium in animal (Diamond et al 1989; Gilman et al 1998) as well as in human (Zamora et al 1998) studies. The histopathologic damage to the proximal tubules is manifest as cytoplasmic vacuolation, interstitial scarring, and destruction of the basal lamina (Gilman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive iron accumulation and apoptosis in the tubulointerstitial region and uranium-induced oxidative stress were reported (Linares et al 2006; Taulan et al 2004). Histological lesions of renal tissue were also observed, mainly in the cortical part of the kidneys (Donnadieu-Claraz et al 2007; Gilman et al 1998; Ortega et al 1989). Gilman et al (1998) reported the lowest threshold of adverse effects for the kidney at 0.03 mg/kg/day, and this threshold was used to establish WHO guidelines for uranium in drinking water (WHO 2004).…”
Section: Biological Effects and Action Mechanismsmentioning
confidence: 99%
“…Histological lesions of renal tissue were also observed, mainly in the cortical part of the kidneys (Donnadieu-Claraz et al 2007; Gilman et al 1998; Ortega et al 1989). Gilman et al (1998) reported the lowest threshold of adverse effects for the kidney at 0.03 mg/kg/day, and this threshold was used to establish WHO guidelines for uranium in drinking water (WHO 2004). In vitro studies demonstrated that uranium alters the expression of genes involved in the cytochromes P450 and glutamate metabolic pathways, cell signaling and trafficking (Prat et al 2010; Vietti and Lasley 2007), and deregulation of the apoptotic process (Prat et al 2010).…”
Section: Biological Effects and Action Mechanismsmentioning
confidence: 99%
“…In addition only a few studies have attempted to characterize the effects of chronic exposure to uranium through drinking water (Gilman et al 1998a, 1998b, 1998c; Kurttio et al 2002; McDonald-Taylor et al 1997; Zamora et al 1998). Although chronic uranium exposure in humans has been clearly associated with increasing urinary glucose, alkaline phosphatase, and β 2 -microglobulin supporting proximal tubule alterations, the urinary albumin levels, which are indicators of glomerular function, are conflicting (Kurttio et al 2002; Zamora et al 1998).…”
mentioning
confidence: 99%
“…Although chronic uranium exposure in humans has been clearly associated with increasing urinary glucose, alkaline phosphatase, and β 2 -microglobulin supporting proximal tubule alterations, the urinary albumin levels, which are indicators of glomerular function, are conflicting (Kurttio et al 2002; Zamora et al 1998). Although both functional and histologic damage to the proximal tubules resulting from acute uranium exposure has been clearly demonstrated (Schramm et al 2002; Sun et al 2002), little is known about the effect of long-term environmental uranium exposure in both humans and animals (Gilman et al 1998a, 1998b, 1998c; Kultima et al 2002; Mao et al 1995; McDonald-Taylor et al 1997; Zamora et al 1998). …”
mentioning
confidence: 99%